2016
DOI: 10.5424/fs/2016253-09476
|View full text |Cite
|
Sign up to set email alerts
|

Future scenarios and conservation strategies for a rear-edge marginal population of Pinus nigra Arnold in Italian central Apennines

Abstract: Aim of the study: To forecast the effects of climate change on the spatial distribution of Black pine of Villetta Barrea in its natural range and to define a possible conservation strategy for the species Area of study: A rear-edge marginal population of Pinus nigra spp. nigra in Abruzzo region, central Italian Apennines Matherials and Methods: For its adaptive and genetic traits this population is considered endemic of the Italian peninsula and represents a rear-edge marginal population of nigra subspecies. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 51 publications
(58 reference statements)
1
17
0
1
Order By: Relevance
“…Mediterranean trees species are classified among many different taxa with a large biodiversity levels that, in part, originated as adaptive responses to previous climate changes ( Benito Garzón et al 2007). Indeed, many recent research efforts have focused on populations living at marginal ecological do-mains in the Mediterranean region (Hampe & Petit 2005, Marchi et al 2016. Both biodiversity conservation and sustainable forest management issues may be supported by the results of this study.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Mediterranean trees species are classified among many different taxa with a large biodiversity levels that, in part, originated as adaptive responses to previous climate changes ( Benito Garzón et al 2007). Indeed, many recent research efforts have focused on populations living at marginal ecological do-mains in the Mediterranean region (Hampe & Petit 2005, Marchi et al 2016. Both biodiversity conservation and sustainable forest management issues may be supported by the results of this study.…”
Section: Discussionsupporting
confidence: 59%
“…Climate change effects have already been observed for tree species and ecological systems (Lindner et al 2010). For example, Boisvert-Marsh et al (2014) reported a latitudinal shift of the distribution of forest species in North America; similar studies have been conducted in Europe and specifically in the Mediterranean region (Marchi et al 2016). Chirici et al (2017) reported the effects of recent, unprecedented wind storms in Italy, and Allen et al (2010) conducted a global review of tree mortality following heat waves and water stresses.…”
Section: Introductionmentioning
confidence: 83%
“…Many environmental and modelling studies are focused on longterm climatic averages (e.g., climatic normal over a 30 years period) to determine the effects of climate change on forest populations (Isaac-Renton et al 2014, Marchi et al 2016. However, an increasing degree of representativeness is needed in studies that require a higher temporal-resolution, such as dendrochronology (Amodei et al 2012, Marchi et al 2015, or studies based on seasonal effects on plant growth (Rathgeber et al 2011, Savi & Fares 2014, Kramer et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the recent decades the climatological aspect gained an increasing attention also in the forestry field due to direct effects on forest resources (Perdinan & Winkler 2014, Schueler et al 2014, Fady et al 2016, Marchi et al 2016), which in turn are fundamental to preserve ecosystem services biodiversity and multi-functionality by means of a sustainable forest management (Di Salvatore et al 2013, Marchetti et al 2014, Salvati et al 2016. Minimum requirements for ecological studies are generally long-term time series of meteorological variables collected in the environment under investigation or at least in forest sites as close as possible to the studied environment.…”
Section: Introductionmentioning
confidence: 99%
“…Error Sin embargo, estudios de modelos de proyección a futuro (2050,2080,2100) para especies de alta montaña concluyen que el cambio climático representa una amenaza innegable para su existencia, además del cambio en el uso del suelo, que representa la causa más grave para su extinción (Keenan, 2016;Marchi et al, 2016). Las especies sensibles a la temperatura pueden responder a un clima cálido moviéndose a lugares más fríos en latitudes o altitudes más altas (Tang et al, 2017).…”
Section: Estimadorunclassified